Workplace Bullying and Intention to Leave: The Moderating Effect of the Organizational Commitment - Rasool, Faheem; ., Ali Hasan; ., Arslan Rafi; ., Abdul Rauf Kashif (Information Management and Business Review, 2013)
The main reasoning of this study is to figure out the relations among workplace bullying and turnover intention of the employee treating organization commitment as a moderating variable. Workplace bullying have a positive impact on intention to leave which reveals the widespread impact that bullying can have on targets in that still less rigorous types of bullying are coupled with victims intention to leave the workplace (e.g. department), the organization or the job. Workplace bullying are more relevant to systematic flaws in the organization and less to employees’ performances while person-related bullying is related more to the personal characteristics of the victims, so irrespective of their commitment, exit from the organization in such circumstances happens to be the preferable alternative for the victim. This study provides an insight that the harmful effects of workplace bullying could be handled effectively through the moderating effects of organizational commitment on the relation between workplace bullying and intention to leave. It therefore, required conducting a further study on the join effects of organizational commitment and bullying in terms of some other variables such as in-role job performance, which are vital to the working of the organizations.